1977
DOI: 10.1007/bf00018772
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and seasonal periodicity of water molds in some lakes in Naini Tal Hills, India

Abstract: The distribution of 26 species of Blastocladiales, Saprolegniales, Lagenidiales and Peronosporales from temperate and sub tropical lakes, situated at different altitude in the same locality, is described . Seasonal periodicity is treated and found to be governed by temperature .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…This agrees with earlier reports (Dayal& Tandon 1963 ;Srivastava 1967 ;Khulbe& Bhargava 1977) . As is evident from Table 6, the frequency percentage of the occurrence of these fungi shows negative and highly significant correlation with the water temperature .…”
Section: Discussionsupporting
confidence: 83%
“…This agrees with earlier reports (Dayal& Tandon 1963 ;Srivastava 1967 ;Khulbe& Bhargava 1977) . As is evident from Table 6, the frequency percentage of the occurrence of these fungi shows negative and highly significant correlation with the water temperature .…”
Section: Discussionsupporting
confidence: 83%
“…The fact that the temperature plays an important role in the occurrence, activity and morphology of aquatic fungi has been emphasized by many aquatic mycologists from different parts of the world (Lund, 1934;Perrott, 1960;Suzuki, 1960a, b;Dayal & Tandon, 1962;Roberts, 1963;Srivastava, 1967;Alabi, 1971a, b;Khulbe & Bhargava, 1977). In the present study, it was found that the fungal occurrence was temperature dependent and it fluctuated with the variation in temperature.…”
Section: Discussionsupporting
confidence: 48%
“…Alabi (1971 la), in his studies on seasonal periodicity of Saprolegniaceae at Nigeria, has classified them into 'all season', 'dry season' and 'rainy season' species. However, Khulbe & Bhargava (1977) used a wider classification. They divided aquatic fungi of Nainital region into four categories viz., constant species (from 10.0-28.5 °C), low temperature species (from 10.0-20.0 °C), moderate temperature species (from 15.0-23.5 °C) and high temperature species (from 15.0-28.5 C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations